Theoretical aspects of difficulties of communicative competence in primary school children with mental retardation - Yu. V. Prilepko; M. N. Alekseeva (Вестник Северо-Кавказского федерального университета, 2023)
This article analyzes the concepts of «competence», «competence», «competence approach», «communicative competence», which largely determine the goals, content, planned results of modern education and criteria for its evaluation. The authors of the article detail the essence and content of communicative competence as one of the main lines of development of younger schoolchildren with mental retardation. The difficulties of developing communicative competence in younger schoolchildren with mental retardation are presented. The aim of the study was to analyze the difficulties of communicative competence in younger schoolchildren with mental retardation. The novelty of the research is determined by the requirements of inclusion to educational processes in educational organizations. The conclusions show that purposeful pedagogical work is needed to develop communicative competence in younger schoolchildren with mental retardation.